The world faces a new viral threat: monkeypox - Bongurala, Archana Reddy; Kadam, Sandhya J.; Nguyen, Vy; Patel, Mira; Sharma, Rishika; Srivastava, Anshuman (International Journal of Contemporary Pediatrics, 2025)
Monkeypox, a zoonotic viral disease, has re-emerged globally, presenting a significant public health challenge. Initially affecting primarily men who have sex with men, the virus has demonstrated broader transmission patterns, raising concerns about its potential to become endemic. The recent outbreak has highlighted the rapid spread of Monkeypox through close contact, particularly during sexual activity. This shift in transmission dynamics necessitates a robust global response, including surveillance systems, contact tracing, and vaccination campaigns. Understanding the virus’s epidemiology, clinical manifestations, and transmission routes is crucial for effective prevention and control. While supportive care remains the primary treatment, antiviral medications and vaccines offer additional tools to mitigate the impact of Monkeypox outbreaks. Continued vigilance and timely interventions are essential to prevent further spread and protect public health.